2020
DOI: 10.3390/antiox9050441
|View full text |Cite
|
Sign up to set email alerts
|

Protein Formulations Containing Polysorbates: Are Metal Chelators Needed at All?

Abstract: Proteins are prone to post-translational modifications at specific sites, which can affect their physicochemical properties, and consequently also their safety and efficacy. Sources of post-translational modifications include oxygen and reactive oxygen species. Additionally, catalytic amounts of Fe(II) or Cu(I) can promote increased activities of reactive oxygen species, and thus catalyse the production of particularly reactive hydroxyl radicals. When oxidative post-translational modifications are detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…As described above, EDTA was reported to prevent iron-induced polysorbate oxidation ( Doyle et al, 2019 ; Kranz et al, 2019 ; Gopalrathnam et al, 2018 ; Bensaid et al, 2022 ; Kranz et al, 2020 ; Yarbrough et al, 2019 ), however, it was also claimed to drive protein oxidation under certain circumstances with ascorbate and Fe 3+ ( Stadtman, 1990 ). Similar behavior was demonstrated by Brovč and colleagues (2020), stressing proteins and polysorbate with Fe 3+ and Cu 2+ in the presence and absence of ascorbate as well as EDTA/DTPA ( Brovč et al, 2020c ). A dependency of OH • formation on chelator and on metal ions could be observed.…”
Section: Oxidation Of Polysorbatesupporting
confidence: 83%
See 2 more Smart Citations
“…As described above, EDTA was reported to prevent iron-induced polysorbate oxidation ( Doyle et al, 2019 ; Kranz et al, 2019 ; Gopalrathnam et al, 2018 ; Bensaid et al, 2022 ; Kranz et al, 2020 ; Yarbrough et al, 2019 ), however, it was also claimed to drive protein oxidation under certain circumstances with ascorbate and Fe 3+ ( Stadtman, 1990 ). Similar behavior was demonstrated by Brovč and colleagues (2020), stressing proteins and polysorbate with Fe 3+ and Cu 2+ in the presence and absence of ascorbate as well as EDTA/DTPA ( Brovč et al, 2020c ). A dependency of OH • formation on chelator and on metal ions could be observed.…”
Section: Oxidation Of Polysorbatesupporting
confidence: 83%
“…Another key characteristic of oxidative degradation is that PS polyesters are significantly more affected by oxidation than monoesters as reported by various stress tests with either H 2 O 2 , AAPH, temperature, or iron ( Borisov et al, 2015 ; Lippold et al, 2017 ; Liu et al, 2022a ; Zhang et al, 2017 ; Kranz et al, 2019 ; Bensaid et al, 2022 ; Zhang et al, 2018 ; Kranz et al, 2020 ; Brovč et al, 2020c ). Via CAD, Kranz and colleagues (2019) showed that higher-order esters of PS20 HP completely disappear after treatment with 10 ppb Fe 2+ at 40 °C after seven days.…”
Section: Oxidation Of Polysorbatementioning
confidence: 96%
See 1 more Smart Citation
“…Nevertheless, to the best of our knowledge, besides a recent paper from our group [ 24 ], this same type of theoretical investigation has not been carried out for the analogous Fe(III)/Fe(II) reduction, and no comparison has been made to the Cu(II)/Cu(I) system for the same set of antioxidants. But this is a relevant topic which has been explored experimentally for various compounds [ 50 , 51 , 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…While a few theoretical studies have evaluated the secondary antioxidant activity (with rate constant calculations) of various organic ligands with respect to the Cu(II)/Cu(I) reduction with and ascorbate, [ 10 , 11 , 26 , 27 , 28 ] to the best of our knowledge, theoretical kinetic studies of secondary antioxidant activity relative to the Fe(III)/Fe(II) reduction, and their comparison with the Cu(II)/Cu(I) redox system, have not been previously reported for any antioxidant. However, this is a topic of relevance that has been studied experimentally for a variety of substrates [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%